Вплив добавки германію у композиті MNіN2S4–Ge на властивості одержуваних тонкоплівкових покриттів - Зінченко, В.Ф.; Чигринов, В.Е.; Мозгова, О.В.; Нечипоренко, Г.В. (Вісник Українського матеріалознавчого товариства, 2016)
The structure and spectral properties of chalcoshpinel MnIn2S4 as well as an influence of germanium additive in CVD-composite on them are studied. It is established that additive of Ge improves optical and operational properties of the thin-film coatings received by thermalevaporation of materials in vacuum.